SERVE : MARKETPLACE FOR SERVICES - Aisha, Norizan (Universiti Malaysia Sarawak, (UNIMAS), 2020)
Since the beginning of time, the best way for a service provider to become successful is to master a skill. The rules were simple - provide a good service and consumers will come. But today, things started to change. To attract consumers, service providers need to be good at enterprising, building connections, using social media, creating ad content and the list goes on. Serve is created to make things simple again, by providing a service marketplace to introduce them to their potential consumers. The way Serve works is service providers will tell about their service. When consumers use Serve for hiring, they will provide specifications of their needs, and Serve will match the right service providers for them. For service providers, Serve features an efficient tool for creating a winning service profile. To get reached by consumers to wishes to hire them, Serve enables consumers to send a quote request and provide details of service specifications and demands. For consumers, Serve features a user-friendly interface that provides limitless listing of service providers for them to browse and compare services.